A Geospatial Cost Comparison of CO2 Plume Geothermal (CPG) Power and Geologic CO2 Storage - Ogland-Hand, Jonathan D.; Adams, Benjamin M.; Bennett, Jeffrey A.; Middleton, Richard S. (Frontiers in Energy Research, 2022)
CO2 Plume Geothermal (CPG) power plants can use gigatonne-levels of CO2 sequestration to generate electricity, but it is unknown if the resources that support low-cost CPG power align with the resources that support low-cost CO2 sequestration. Here, we estimate and compare the geospatially-distributed cost of CPG and CO2 storage across a portion of North America. We find that the locations with lowest-cost CO2 storage are different than the locations with lowest-cost CPG. There are also locations with low-cost CO2 storage (<$5/tCO2) that do not support CPG power generation due to insufficient reservoir transmissivity or temperature. Thus, CPG development may require electricity prices that are greater than the levelized cost of electricity (LCOE) to offset the increased cost of sequestration. We introduce the “Additional Cost of Electricity (ACOE)” metric to account for this cost and add it to the LCOE to calculate breakeven electricity prices that are required for CPG development. We find that breakeven prices are lower when new CO2 injection wells are drilled specifically for CPG (i.e., “greenfield” CPG development) compared to if only existing CO2 sequestration injection wells are used (i.e., “brownfield” CPG development). This is because comparatively few wells are needed for sequestration-only, and the increased power capacity from having more CPG wells outweighs the increased costs from more drilling. We also find that sequestered CO2 could be used to approximately triple the United States geothermal electricity power capacity via a single CPG “sweet spot” in South Dakota, but that breakeven electricity price for this development is on the order of $200/MWeh.